Factors that influence deviance workplace behavior among staff around Seberang perak / Norjamilah Ishak - Ishak, Norjamilah (2019)
The deviance behaviour is one issue that have in every organization. Therefore, 5 independence variable was used for identified their significant with dependent variable. This study investigated the factor of influence deviance behaviour among staff around Seberang Perak. The objectives of the study were (1) to describe the relationship between factor of leadership and deviant workplace behaviour (2) to describe the relationship between factor of ethic climate and deviant workplace behaviour (3) to describe the relationship between factor of antisocial behaviour and deviant workplace behaviour (4) to describe the relationship between factor of decision making and deviant workplace behaviour (5) to describe the relationship between factor of moral behaviour and deviant workplace behaviour. Based on this research, the researcher was distributed 187 of the questionnaires for several organization in Seberang Perak to identify the relationship of staff from all level and whether the deviance behaviour was in major problems to improve performance. The methodology that was employed in this study was simple random sampling for collected the data and data that successful collected was 160 from 6 organization. From the result in regression shows a 2 variables which ethic climate had significant and negative relationship while decision making was significant and positive relationship among 5 variables with deviance work behaviour.